Mexican registry of pediatric cardiac surgery. First report - Jorge Cervantes-Salazar; Juan Calderón-Colmenero; Samuel Ramírez-Marroquín; Alexis Palacios-Macedo; Alejandro Bolio Cerdán; Alfredo Vizcaíno Alarcón; Pedro Curi-Curi; Manuel de la Llata; Julio Erdmenger Orellana; Julieta González; Federico García Soriano; Alejandro Calderón; et al. (Permanyer, 2014)
Background: Currently, there is a spreading worldwide tendency to characterize health issues and to propose alternative solutions via the creation of computerized databases. The aim of this study was to present the results in a computerized database of pediatric cardiac surgeries developed under the auspices of the Mexican Association of Specialists in Congenital Heart Diseases (Asociación Mexicana de Especialistas en Cardiopatías Congénitas A.C) and coordinated by the collegiate group of Pediatric Cardiology and Surgery as petitioned by the National Institutes of Health and High Specialty Hospitals Coordinating Commission. Methods: We analyzed all cases registered in the database during a 1-year observation period (August 1, 2011 to July 31, 2012) by all major Health Ministry-dependent institutes and hospitals offering surgical services related to pediatric cardiopathies to the non-insured population. Results: Seven institutions participated voluntarily in completing the database. During the analyzed period, 943 surgeries in 880 patients with 7% reoperations (n = 63) were registered. Thirty-eight percent of the surgeries were performed in children <1 year of age. The five most common cardiopathies were patent ductus arteriosus (n = 96), ventricular septal defect (n = 86), tetralogy of Fallot (n = 72), atrial septal defect (n = 68), and aortic coarctation (n = 54). Ninety percent of surgeries were elective and extracorporeal circulation was used in 62% of surgeries. Global mortality rate was 7.5% with the following distribution in the RACHS-1 score categories: 1 (n = 4, 2%), 2 (n = 19, 6%), 3 (n = 22, 8%), 4 (n = 12, 19%), 5 (n = 1, 25%), 6 (n = 6, 44%), and non-classifiable (n = 2, 9%). Conclusions: This analysis provides a representative view of the surgical practices in cardiovascular diseases in the pediatric population at the national non-insured population level. However, incorporating other health institutions to the national registry database will render a more accurate panorama of the national reality in surgical practices in the population <18 years of age.